Historical dictionary of Buddhism: Historical dictionaries of religions, philosophies, and movements; no.1 - Charles S Prebish (The Scarecrow, 1993)
The book provides a comprehensive guide for interested readers and initiates alike. It includes several hundred entries on sigificant persons, places, events, texts, doctrines, practices, institutions, and movements. It inserts in the broader context of an introduction and the historical perspective of a chronology, features. But, given the linguistic complexities, the book adds a pronunciation guide and a very useful overview of the Buddhist scriptures